2020
DOI: 10.3390/biomedicines8120555
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 18F-Choline PET/CT in Patients with Metastatic Castration-Resistant Prostate Cancer Treated with Radium-223

Abstract: We aimed to investigate the role of positron emission computed tomography (PET/CT) with 18F-choline for predicting the outcome of metastatic castration-resistant prostate cancer (mCRPC) submitted to treatment with Radium-223 (223Ra-therapy). Clinical records of 20 mCRPC patients submitted to PET/CT with 18F-choline before 223Ra-therapy were retrospectively evaluated. The following PET-derived parameters were calculated: number of lesions, maximum and mean standardized uptake values (SUVmax, SUVmean), lean body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…On the other hand, many studies already showed the prognostic value of circulating PSA and ALP at baseline, as biochemical indicators of the tumor extent [28,[31][32][33][34][35][36][37][38]. This is coherent with the unfavorable prognosis observed in patients with massive bone metastases (> 20) at the bone scan or high tumor burden assessed with more sophisticated quantification approaches [32,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, many studies already showed the prognostic value of circulating PSA and ALP at baseline, as biochemical indicators of the tumor extent [28,[31][32][33][34][35][36][37][38]. This is coherent with the unfavorable prognosis observed in patients with massive bone metastases (> 20) at the bone scan or high tumor burden assessed with more sophisticated quantification approaches [32,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 83%
“…As previously mentioned, data from the TheraP and VISION trials support the notion that patients with significant PSMA-PET uptake are those expected to derive the greatest benefit from Lu-PSMA [ 27 , 68 ]. Some studies suggest that FDG- and choline-PET can adequately identify patients who better respond to treatment with ARSi and radium-223 in the mCRPC setting [ 161 , 162 , 163 ]. However, prospective studies are warranted to determine that the early identification of response/progression—not detected by standard imaging—is clinically useful and could affect the prognosis of patients.…”
Section: Predictive Biomarkers and Potential Impact On Treatment Sequencementioning
confidence: 99%
“…[ 18 F]Choline and [ 68 Ga]PSMA-11 PET/CT as gatekeepers for the treatment of metastatic PCa with Radium 223 were assessed in three papers. The groups of Filippi [ 47 ] and Garcia Vicente [ 48 ] assessed 11 and 40 patients, retrospectively, who underwent PET/CT with [ 18 F]Choline before [ 223 Ra]dichloride treatment. They stated that the presence of extra-osseous disease at PET/CT was correlated with a poor outcome and also a high SUV max (in at least five sites).…”
Section: Resultsmentioning
confidence: 99%